Relationships between fluid‐rock interactions and the electrical conductivity of sandstones. Issue 7 (12th July 2013) - Schepers, A.; Milsch, H.
<x xml:space="preserve">Abstract</x> [1] Batch and flow‐through experiments were performed on quartz‐feldspar granular aggregates and sandstone samples to investigate time‐dependent effects of fluid‐rock interactions on fluid and rock conductivity, respectively. The experiments were conducted at temperatures up to 164 °C, at confining and pore pressures up to 10 and 5 MPa, respectively, and for up to 136 days. It showed that changes in rock conductivity were unequivocally related to changes in pore fluid conductivity. It is inferred that these changes were dependent on kinetically controlled dissolution reactions between the mineral grains and the fluid. The time‐dependent signature of rock conductivity implied a detectable transition from initial dissolution toward some state of equilibrium. The response of rock conductivity to temperature changes followed an Arrhenius‐type behavior. An exploratory kinetic evaluation of the conductivity data for sandstone samples yielded an apparent activation energy <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3x8cbdjc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Ea∗</alternatives> of approximately 32 kJ/mol. A concurrent chemical fluid analysis showed that this is an integrated value over all reactions occurring in parallel within a sample. These reactions namely concern silica and silicate dissolution but also the dissolution of accessory salt minerals. It is concluded that measuring the evolution of rock conductivity in combination with chemical pore fluid analysis constitutes a powerful and quantitative tool for monitoring time‐dependent changes in pore fluid chemistry and thus fluid‐rock interactions in real time.